Organizational Structure Change and Hybridity: Enhancing Uncertainty as a Response to Competing and Changing Institutional Logics - Liu, Liming; Zhang, Chao (Frontiers in Psychology, 2022)
Confronting the uncertain environment, this article takes mass media organizations as a critical case to answer the question how the perception of uncertainty in the institutional environment affects the adaptation of organizational structure in pursuing legitimacy for hybrid organizations. The theoretical framework re-conceptualizes the term of “uncertainty” with two key concepts of “institutional competition” and “institutional change” to analyze the interactive relationship between organizational behavior and institutional environment. Based on the empirical data collected from two-staged fieldwork and in-depth interviews, the case analysis indicates that in the face of competing and changing institutional logics, Chinese mass media organizations have gradually shifted from a blending strategy in the exploration stage to a compartmentalizing strategy in the stable stage. And the hybrids can deal with the uncertainty of the institutional environment by enhancing the uncertainty of the organizational structure. Finally, the case evolves an organizational integration on the basis of internal legitimacy. It manifests a possibility for hybrids of combining the two major response mechanisms in one process.